Induction of multiple ovulations in mares using low doses of GnRH agonist Deslorelin Acetate at 48 hours after luteolysis - Azevedo, Marlon V.; Souza, Natalia M.; Ferreira-Silva, Jose C.; Batista, Ilana O.; Moura, Marcelo T.; Oliveira, Marcos A. L.; Alvarenga, Marco A. [UNESP]; Lima, Paulo F. (Hippiatrika Verlag Mbh, 2015)
This study was aimed to test low doses of a GnRH agonist, deslorelin acetate (DA), for induction of multiple ovulations in mares and to determine its impact upon their reproductive efficiency. Seven mares aging from 8-20 years were used in three consecutive reproductive cycles. Mares were initially monitored by ultrasound irrespectively of cycle stage, inseminated and submitted to embryo collection (EC) (T1). Immediately after, mares received 7.5 mg dinoprost tromothamine (DT) and were monitored by ultrasound twice a day until larger follicle reached 23-25mm and the second >18mm (T2). At this time point, mares received 100 mu g DA and ovulation was induced with 1000 mu g DA and 1000IU hCG when largest follicle reached 33-35mm in diameter, followed by EC. Mares were further allocated to T3 when received 7.5 mg DT after EC on 12 and 100 mu g DA 48 h later. DA treatment was performed until dominant follicle reached 34 +/- 1 mm or 6 days of application. All EC were performed 8 days after ovulation. Mares with multiple ovulations in T1, T2 and T3 were 14.28% (1/7), 100.00% (7/7) and 0.00% (0/7), respectively, and averaged 0.43 +/- 0.53 in T1, 0.86 +/- 0.38 in T2 and 0.00 in T3 embryos per donor, respectively. Embryo recovery rate was 43.00% in T1, 85.71% in T2 and 0.00% T3. In conclusion, use of DA in mares with follicles larger than 25mm enhanced dominant and co-dominant follicle growth, that ultimately increased the incidence of multiple ovulations and embryo recovery rate.
Keywords: Super-ovulation; Gonadotropin; Hormone; Embryo transfer; PGF2; Reproduktion